Influencia del sexo, edad, año y efectos maternos aditivos y permanentes sobre características de importancia económica en alpacas Huacaya - Trillo Zárate, Fritz (2021)
The aim of this study was to estimate the additive and permanent maternal effect, age, sex and year of the campaign on the body weights at birth, weaning and first shearing and fleece weight in Huacaya alpacas from the La Raya Research and Production Centre in Puno, Peru, at an altitude between 4100 and 5000 above the sea level. In total, 1494 sheared offspring corresponding to two campaign periods were evaluated. The productive characteristics were subjected to a mixed model, where the campaign and the sex of the calf were adjusted with their age at weaning and first shearing and included as fixed effects. The random effects were maternal additive genetic value and mother's age as permanent maternal effects. The variance components were estimated by the Restricted Maximum Likelihood (REML). The average age of tuis alpacas at weaning was 240.1 ± 0.3 days, while the age at first shearing was 278.7 ± 0.3 days, during which they had a linear growth of 0.11-0.12 kg of body weight increase. The maternal heritability was 0.32 ± 0.058, 0.49 ± 0.050, 0.39 ± 0.056 and 0.19 ± 0.064 for the body weights at birth, weaning and first shearing and fleece weight, respectively. The campaign had an influence on the productive characteristics evaluated, while the sex of the offspring was preponderant only at weaning, with the females being the best performers. The additive and permanent maternal genetic effects were more prevalent in body weight of the animal compared to its fleece weight.